academic libraries embrace Web access (Information Research: An International Electronic Journal)
This article presents the lessons learned when six universitiesin the West Midlands, UK worked collaboratively within the eLib (Electronic Libraries Programme). These libraries and learning resource centres spent two years focused on a culture change in the support provided to education, law, and life sciences subject departments. Their efforts resulted in a mediation Model for networked information. The project manager for TAPin reflects upon the importance of attitudes, infrastructure, staff skills, appearances and service practices in the process of change.